Pembelajaran Bahasa Inggris Dasar Tema Makanan Bergizi Menggunakan Augmented Reality Berbasis Android (International Forum of Researchers and Lecturers, 2023)
Knowledge is one of the human links to perfection. The human tendency to crave makes him always move forward to become better from time to time. One of the enthusiastic actions of humans is illustrated by the development of technology and information that makes work easier. Learning at SDN Durman 049 is still conventional learning that is less interesting or less effective when in the current state of online learning. Ar food application was created to facilitate and be an alternative in learning at SDN Durman 049 especially for grade IV. AR food is an androd based Augmented ReaIity technology app that contains food in English. Android operating system devices are the most widely used devices today. AR food is proven to help learn English for grade IV in online conditions like this, in addition to adding alternatives in learning AR food increases the effectiveness of online learning. AR food displays 3D English food by scanning the marker using the camera and a 3D object of English food will appear above the marker.